Retirement, learning and the role of Higher Education. Issue 5 (2nd September 2016) - Jamieson, Anne
Abstract: This article brings together some of the main findings from research on older learners, conducted and published by the author over a period of 10 years. This research investigated the characteristics, motivations and benefits of formal learning. The samples were drawn from among both students and graduates from a London university. Data were collected both through questionnaire surveys, including a follow-up study, and life history interviews. The material collected was analysed in a variety of ways, building up a picture of the meanings of formal learning for different individuals and at different points of the life course, including retirement. The author, having herself retired and become 'an older learner', ends with a discussion of the meanings of learning in her own retirement, in the context of her research findings.